Outcomes of COVID-19 Among Hospitalized Patients With Non-dialysis CKD - Coca, Armando; Burballa, Carla; Centellas-Pérez, Francisco Javier; Pérez-Sáez, María José; Bustamante-Munguira, Elena; Ortega, Agustín; Dueñas, Carlos; Arenas, María Dolores; Pérez-Martínez, Juan; Ruiz, Guadalupe; Crespo, Marta; Llamas, Francisco; et al. (Frontiers in Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome-Corona Virus 2 has generated significant impact on global health worldwide. COVID-19 can cause pneumonia and organ injury. Chronic kidney disease (CKD) has been associated with increased mortality in previous epidemics, but there is a paucity of data regarding actual risks for non-dialysis CKD patients with COVID-19. Methods: Multicenter, observational cohort study including 136 non-dialysis CKD patients and 136 age- and sex-matched controls that required hospitalization due to COVID-19. Patients with end-stage renal disease, a kidney transplant or without registered baseline glomerular filtration rate prior to COVID-19 infection were excluded. CKD and acute kidney injury (AKI) were defined according to KDIGO criteria. Results: CKD patients had higher white blood cell count and D-dimer and lower lymphocyte percentage. No differences were found regarding symptoms on admission. CKD was associated with higher rate of AKI (61vs24.3%) and mortality (40.4vs24.3%). Patients with AKI had the highest hazard for death (AKI/non-CKD HR:7.04,95%CI:2.87-17.29; AKI/CKD HR:5.25,95%CI: 2.29-12.02), followed by CKD subjects without AKI (HR:3.39,95%CI:1.36-8.46). CKD status did not condition ICU admission or length of in-hospital stay. Conclusions: CKD patients that require hospitalization due to COVID-19 are exposed to higher risk of death and AKI.